Keragaan Karakter Agronomi Beberapa Genotipe Tomat (Lycopersicum esculentum Mill.) di Dataran Rendah - ', Sumiasih; ', Murniati; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This objective of the study is to determine the performance of some tomato genotypes, agronomic characters in low land. The experiment was conducted from June to October 2013 et experiment yield, Agriculture Faculty University of Riau. The experiment used randomized block design (RBD) with three replications. The treatments were 9 genotype i.e. IPB 13 x IPB 3,IPB 64 x IPB 3,IPB 64 x IPB 13, IPB 78 x IPB 3,IPB 78 x IPB 13, IPB 78 x IPB 64, Permata, Jawara and Fortuna. The parameters are plant height, stem diameter, flowering date, harvesting date, fruit length, fruit diameter, number of fruit cavities, fruit flesh thicness, number of fruit per plant, weight per fruit and total fruit weight per plant. The results showed that genotypes significantly affected all of the parameter except stem diameter. IPB 78 x IPB 64 had the highest fruit length, fruit diameter, fruit flesh thicness, weight per fruit and total fruit weight per plant. Key word: Performance, tomato, low land